PENGARUH STRATEGI PEMBELAJARAN FIRE-UP TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN KIMIA (Pokok Bahasan Koloid Di SMAN 1 Cerenti) - Nelta Aulia; Dwi Putri Musdansi; Asregi Asril (Universitas Islam Kuantan Singingi, 2020)
This research is motivated by the way of learning that still uses the Teacher Center Learning learning model so that students are still less actively involved as well as a rigid learning atmosphere so that students quickly feel bored and lack enthusiasm in following the learning process. One method for students to be active in learning is to use the FIRE-UP Learning Strategy. The objectives of the research to determine student learning outcomes on the subject of colloids in the XI MIPA class of SMA Negeri 1 Cerenti. This research was a quantitative research type of quasi-experimental design with a posttest-only control design experimental design. The sample of this research was students of class XI MIPA2 as an experimental class and class XI MIPA3 as a control class. The sampling technique is the cluster random sampling technique. Data collection in this study uses written documentation and tests. To determine the normality of the data used Chi-Square test, variance test to determine the homogeneity of the data, and the final data analysis in this study using the